THE LOCATION OF THE PASSENGER TRAINS STATIONS FOR STOPPING IN BIG CITIES AND URBAN AGGLOMERATIONS - G. Sviridchuk (Вестник университета)
The article shows the planning targets in the scope of the transport node and city. The ways of railway stations development as places of mass transfer of passengers is determined. The method of identifying dependencies between the length of foot walk and increasing the number of stations for stopping is proposed.